Antihypertensive therapy adherence among hypertensive patients from Bragança county, Portugal - Pinto, Isabel C. (2018)
Hypertension increases the risk of cardiovascular diseases and is highly prevalent worldwide, reaching more than a quarter of the Portuguese population. Poor antihypertensive therapy adherence has been identified as the main cause of failure to control hypertension. Objectives: To estimate the prevalence of antihypertensive therapy adherence and related factors. Methods: This cross-sectional study was based on a questionnaire, with MAT scale (measure of adherence to therapy) validated for the Portuguese population (Delgado & Lima, 2001), applied to 122 hypertensive patients from Bragança county, in northern Portugal. To assess therapy adherence, those whose average adherence levels were ≥5 were called adherent. It was used descriptive statistics, correlations were accessed using qui-square test, with a significance level of 5%. Results: The sample consisted mainly of females (59,1% vs. 40.9%), aged between 31 and 92 years old (mean 69.8). The participants show high antihypertensive therapy adherence level (82,8%). Only marital status is related to therapy adherence, being married or widowed who least adhered to antihypertensive treatment (p=0.04). Conclusions: This study shows that a high prevalence of hypertensive patients adhered to antihypertensive therapy prescribed, being married or widowed who least adhered to treatment.